Designing 3D-printed concrete with ternary blended mortars incorporating fly ash and silica fume: effects of low water-binder ratios on workability and strength - Kamrul, Hasan; Aizat, Alias; Fadzil, Mat Yahaya; Khairul Fikri, Muhammad; Hasan, Mehedi (Springer, 2026)
3D-printed concrete (3DPC) construction has gained global attention as an innovative and promising technique. However, the high cement content in 3DPC raises sustainability concerns, presenting a challenge for implementing sustainable processes. To address the issue, this research uses a low water-to-binder (w/b) ratio and incorporates silica fume (SF) and fly ash (FA) as partial cement replacements to reduce cement consumption and enhance sustainability. Three w/b ratios (0.33, 0.35, 0.37) and varying superplasticizer (SP) doses (0%, 0.25%, 0.5%, 0.75%, 1%) were tested, with 10% SF and 20% FA. The study investigated the physical, chemical, and morphological properties of the mix, alongside fresh, hardened, and durability properties, including workability, dry bulk density, compressive strength, dynamic modulus of elasticity, water absorption, and sulfate resistance. The results showed that a higher w/b ratio increased workability, with the w/b 0.37 mix exhibiting 50.71% higher workability than the w/b 0.33 and 45.09% higher than the w/b 0.35 for SP0 at 0 min. Besides, both a lower w/b ratio and increased SP content improved dry bulk density, compressive strength, and dynamic modulus of elasticity, with performance peaking at a 0.5% SP dosage in mix SP2. Additionally, reducing the w/b ratio decreased water absorption from 5.54% at 0.37 to 4.22% at 0.33 and lowered mass loss across all mixes; notably, the 0.33 mix with SP2 achieved the lowest mass loss (0.89%) and strength loss (3.12%). Despite these improvements, the use of SP increased production costs by 14.32%, while CO2 emissions rose only slightly by 0.89%.